2022
DOI: 10.3389/fimmu.2022.890166
|View full text |Cite|
|
Sign up to set email alerts
|

Development of Immunotherapy Strategies Targeting Tumor Microenvironment Is Fiercely Ongoing

Abstract: Tumor immune microenvironment is a very complex system that is influenced by a wide range of factors; in this microenvironment, various immune cells, stromal cells, and cytokines can interact with tumor cells and jointly regulate this complex ecosystem. During tumor development, the tumor microenvironment (TME) shows the upregulation of inhibitory signals and downregulation of activating signals, which result in an immunosuppressive microenvironment and lead to tumor immune escape. In recent years, a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…For instance, metabolic interventions that promote the glycolytic or mitochondrial pathways in TILs can improve their persistence and effector functions in the tumor microenvironment. 100,101 When combining immunometabolism and immunotherapy, it is essential to consider timing, dosage, and administration order.…”
Section: Combination Therapies: Immunometabolism and Immunotherapymentioning
confidence: 99%
“…For instance, metabolic interventions that promote the glycolytic or mitochondrial pathways in TILs can improve their persistence and effector functions in the tumor microenvironment. 100,101 When combining immunometabolism and immunotherapy, it is essential to consider timing, dosage, and administration order.…”
Section: Combination Therapies: Immunometabolism and Immunotherapymentioning
confidence: 99%
“…More attention should be focused on seeking combination strategies for modulating TME. 6 There is promising evidence of the effectiveness of bacteria/bacteria-derived membrane particles in the modulation of TME/TAM and the controlled targeted drug delivery to cancer. They can overcome physical barriers, target and accumulate in tumor tissues and initiate antitumor immune responses.…”
Section: Abstract Dmentioning
confidence: 99%
“…Nevertheless, the effectiveness of immunotherapy varies greatly among different populations, tumors, and individuals, and only a fraction of patients benefit from the treatment (Wang et al, 2021). Studies have demonstrated that tumor immune microenvironment (TIME) plays essential roles in the pathogenesis of cancer, and its heterogeneity determines the immunotherapeutic effect to a certain extent (Bai and Cui, 2022). Therefore, significant efforts have been made to identify reliable predictive biomarkers of response and resistance to immunotherapy.…”
Section: Introductionmentioning
confidence: 99%